2019
DOI: 10.3390/ijms20061508
|View full text |Cite
|
Sign up to set email alerts
|

Tomentosin Displays Anti-Carcinogenic Effect in Human Osteosarcoma MG-63 Cells via the Induction of Intracellular Reactive Oxygen Species

Abstract: Tomentosin is a natural sesquiterpene lactone extracted from various plants and is widely used as a medicine because it exhibits essential therapeutic properties. In this study, we investigated the anti-carcinogenic effects of tomentosin in human osteosarcoma MG-63 cells by performing cell migration/viability/proliferation, apoptosis, and reactive oxygen species (ROS) analysis assays. MG-63 cells were treated with various doses of tomentosin. After treatment with tomentosin, MG-63 cells were analyzed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Thus, under oxidative stress conditions, biomolecules may undergo the attack of ROS and get oxidized. Most of the time, such phenomena are deleterious for cells, but in some case, inducing an overproduction of ROS can help kill cells such as cancer cells [24].…”
Section: Production Of Rosmentioning
confidence: 99%
“…Thus, under oxidative stress conditions, biomolecules may undergo the attack of ROS and get oxidized. Most of the time, such phenomena are deleterious for cells, but in some case, inducing an overproduction of ROS can help kill cells such as cancer cells [24].…”
Section: Production Of Rosmentioning
confidence: 99%
“…After 24 h of incubation, the cells were treated with acetylshikonin at a concentration gradient of 0 to 10 μM and incubated for 24, 48, and 72 h for the time-dependent response assay. After 24, 48, and 72 h of treatment, a 20 μL MTT dye solution (5 mg/mL in phosphate buffer) was added to each well and the incubation for 2 h. After all the media were removed, formazan was solubilized in 200 μL DMSO, and light absorbance was measured at a wavelength of 570 nm using a microplate reader [31].…”
Section: Mtt Cell Viability Assaymentioning
confidence: 99%
“…13 Furthermore, our laboratory reported that tomentosin induces apoptosis in osteosarcoma cancer cells by generating reactive oxygen species. 30 However, the anticarcinogenic effects of tomentosin in HCC have not been studied well.…”
Section: Discussionmentioning
confidence: 99%